GLOBAL DEOFFSHORIZATION: BASIC APPROACHES AND OBSTACLES TO THEIR IMPLEMENTATION - I. V. Tsvigun; D. S. Kostyuchenko; M. V. Chigir (Дискурс, 2018)
The rapid growth of offshore economy in the recent decade is a sign of insufficiency of international measures aimed at fighting capital drain to offshore jurisdictions. It is quite necessary to find relevant contemporary approach to deoffshorization of the global economy. The article provides an overview of the projects of global deoffshorization that are currently implemented (automatic tax information exchange, the global register of legal entities, OECD country-by-country reporting requirements), as well as the prospective projects (the global financial register, a unitary approach to TNC taxation). Positive and negative sides of each project together with their implementation prospects are estimated.